KESADARAN DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK MEMBAYAR PAJAK BUMI DAN BANGUNAN (STUDI DI WILAYAH KECAMATAN PASEH KABUPATEN BANDUNG) - Dhea Amelia Syafilla; Siti Ganiah Maulany; Anisa Yuniarti (Jurnal Akuntansi, Auditing dan Keuangan Syariah, 2022)
This study aims to determine and analyze the effect of taxpayer awareness and knowledge of taxation on taxpayer compliance in paying property taxes. The data used in this study is primary data by distributing questionnaires to PBB taxpayers in Kecamatan Paseh Kabupaten Bandung. The population in this study was to use a sample of 100 people who were PBB taxpayers in Kecamatan Paseh. The sampling technique in this study used the convenience sampling method. In this study, the data analysis technique used is multiple linear regression analysis and the tool it uses is SPSS 21 software. This study shows that taxpayer awareness partially has a positive and significant effect on property taxpayer compliance, and tax knowledge partially positive and significant effect on property taxpayer compliance. Simultaneously, taxpayer awareness and tax knowledge have an effect on property taxpayer compliance by obtaining a coefficient of determination of 0.250, therefore taxpayer awareness and tax knowledge have an effect of 25% on taxpayer compliance and the rest is influenced by other factors not examined in this studythis research.